Molecular structure upon compression and stability toward oxidation of Langmuir films of unsaturated fatty acids a vibrational sum frequency spectroscopy study - Tyrode, Eric (Langmuir : the ACS journal of surfaces and colloids, 2010)
Vibrational sum frequency spectroscopy (VSFS) has been used to determine the stability toward oxidation in air of a series of unsaturated fatty acids, measuring as a function of time the changes in the chemical structure and conformational order of films spread on a Langmuir trough. The fatty acids studied consisted of a 20-carbon backbone with increasing numbers of cis double bonds in the chain: 11c-eicosenoic acid (20:1 EA, omega-9), 11c,14c-eicosadienoic acid (20:2 EA, omega-6), and 11c,14c,17c-eicosatrienoic acid (20:3 EA, omega-3). Measurements at constant surface pressure show that double bonds are lost from the surface region and that drops in intensity of the vinyl CH stretch are detectable within a few minutes of spreading the monolayer. The results are consistent with the fatty acid peroxidation free radical mechanism. The sum frequency spectra also reveal that what remains on the surface is conformationally more disordered with a larger number of gauche defects. The oxidation kinetics are found to be strongly dependent on the packing density of the monolayer, being more stable at higher pressures. Oxidation can be avoided by purging the system in an inert atmosphere. Finally, the molecular structure upon compression was tracked in unoxidized monolayers. The results suggest that the packing and orientation of the double bond sections of all three unsaturated fatty acids show remarkable similarities, with the direction of the double bonds approximately parallel to each other irrespective of the number of unsaturations in the chain, with the 20:3 EA probably forming "iron-angle" structures. The possibility of unsaturated chains in a "hairpin" configuration is discarded for area per molecules smaller than approximately 50 A(2), which corresponds to the lowest surface pressure measured with VSFS